The weighted sum preferred levels of performances approach to solving problems in human resources management - Karabasevic, Darjan; Stanujkic, Dragisa; Djordjevic, Bojan; Stanujkic, Ana (Serbian Journal of Management, 2018)
In the modern market and in competitive business conditions, human resources are the basis of achieving a long-term success and the key resource of competitive advantage. Therefore, employees represent one of the main strategic resources of an organization. The process of the recruitment and selection of personnel plays an extremely important role in human resources management, which tends to provide an organization with motivated and competent personnel. Therefore, the main objective of the paper is to present an approach to solving problems in human resource management, i.e. personnel selection, based on a recently developed multiple-criteria decision making method. The methodology used in the paper is based on the Weighted Sum Preferred Levels of Performances (WS PLP) method adapted for the purpose of an analysis based on decision-makers’ preferred levels of performances. The weights of the criteria are determined by using the Step-wise Weight Assessment Ratio Analysis method (the SWARA method). The final ranking order is established by using the weighted averaging operator. Usefulness and efficiency of the proposed approach are considered in the numerical example for the selection of the HR manager. As a result, WS PLP approach can be used for solving personnel selection problems. The proposed multiple-criteria decision-making based approach is easy to use, effective, applicable and adaptable, depending on the goal we want to achieve. In order to solve problems in other areas, the proposed approach can be easily modified.